Perceptions of mental toughness in elite swimmers: a Q methodology study - Kesler, A.; Yildiz, Y.; Sevilmis, U.; Küçükalpelli, F.; Gülsen, D. B. A. (Frontiers in Psychology, 2026)
This study aimed to understand the perceptions of mental toughness among elite swimmers. A qualitative research method, the Q methodology, was employed to delve into the individual perspectives of participants. Data were analyzed using the PQ Method software to identify participants` perceptions of mental toughness. The study involved 23 elite swimmers (16 males and 7 females), all of whom had qualified for the Turkish National Swimming Championships. Participants represented a range of swimming disciplines, including freestyle, breaststroke, butterfly, and backstroke. The findings indicate that participants grouped their views on mental toughness into three main factors. The first factor reflected a determined attitude towards overcoming challenges and achieving goals. The second emphasized the importance of learning from mistakes and valuing feedback from coaches. The third revealed athletes` ability to stay calm under pressure, alongside their sensitivity to coaches` evaluations. These three distinct perspectives demonstrate that mental toughness is not a singular concept but rather a multidimensional construct influenced by personal resilience, interpersonal dynamics, and emotional regulation. Together, these viewpoints indicate that mental toughness is represented through multiple psychological and relational dimensions within this sample.